Uniform roasting method for 500KA full-graphitization electrolytic cell

The method addresses uneven roasting and conductivity issues in 500KA electrolytic cells by optimizing graphite-to-coke ratios and using controlled voltage/temperature gradients, ensuring uniform roasting and improved cell stability.

CN119243258APending Publication Date: 2025-01-03HEQING YIXIN ALUMINIUM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446358.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing methods for roasting 500KA fully graphitized electrolytic cells face issues with uneven temperature distribution, poor conductivity at corner electrodes, and insufficient roasting of cathode linings, leading to early damage and reduced cell life.

Method used

A method involving specific ratios of graphite and coke powder for corner and middle poles, combined with cryolite-filled grooves and controlled voltage/temperature gradients, along with multiple material layers and flexible connections, ensures uniform roasting and improved conductivity.

Benefits of technology

Achieves uniform temperature distribution, enhances conductivity, and extends the life of the electrolytic cell by preventing thermal stress and reducing material costs, while maintaining stable anode current distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243258A_ABST
    Figure CN119243258A_ABST
Patent Text Reader

Abstract

The invention provides a uniform roasting method for a 500KA full-graphitization electrolytic cell, and relates to the technical field of electrolytic cell roasting. The roasting method comprises the steps that grooves between cathode carbon blocks are filled and leveled up with cryolite wrapped with a plastic film, a medium is laid on the surface of a cathode boss, a mixture of graphite scraps and coke powder with the mass ratio being 1: 6 is laid on corner poles, pure coke powder is laid on an intermediate pole, and the laying thickness is 20 mm; filling calcium fluoride, cryolite, sodium carbonate and electrolyte powder into a tank; electrifying and roasting. Through the method, the conductivity of the corner pole can be improved, the current distribution is uniform, the corner pole and the cathode lining are fully roasted, the stability of the electrolytic cell is enhanced, and the service life of the electrolytic cell is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic cell roasting, and in particular to a method for uniformly roasting a 500KA fully graphitized electrolytic cell. Background Art

[0002] The roasting of the electrolytic cell is a key management period before the electrolytic cell enters the startup stage. Scientific and reasonable roasting of the aluminum electrolytic cell can make the electrolytic cell smoothly enter the normal and stable production stage, avoid early damage, and help extend the life of the electrolytic cell. The pre-baked anode electrolytic cell is mainly fired into the cathode during the roasting process. The purpose is to sinter and coke the cathode carbon block, the side carbon block, the carbon inter-paste, the surrounding paste, etc., so that the cathode bottom carbon block and the side carbon block are burned into a whole, remove the moisture and volatiles in the lining, and evenly increase the lining temperature.

[0003] Patent No. CN111020636A discloses a method for starting and loading a 500KA aluminum electrolytic cell for roasting. The materials used for loading the furnace are quantified. The furnace bottom is loaded with a mixture of forged coke particles and graphite in two different proportions. The electrolyte fragments and high molecular ratio cryolite are used for full-cavity loading. The roasting temperature changes evenly and steadily during the roasting process, thereby improving the roasting effect. The disadvantage is that the corners of the graphite and coke particles are not fully roasted under the above ratio, and the overall temperature rise of the cathode lining is uneven.

[0004] Patent No. CN103046078A discloses a method for starting a roasting of a cylindrical convex cathode aluminum electrolytic cell, (1) placing a coke particle laying frame around a boss, and then laying a layer of coke particles on and around the boss surface, the layer of coke particles being in the coke particle laying frame and flush with the coke particle laying frame; (2) laying an electrolyte layer around the coke particle laying frame, and then laying a coke particle layer on the electrolyte layer, and at the same time, compacting and flattening the space on the cathode upper surface that is not filled and flattened with coke particles; (3) after laying, placing the anode flat on the upper surface of the coke particle layer on the boss; (4) installing the anode, setting a temperature measuring point in the gap between the anodes, and then filling the middle gap of the anode with cryolite powder for 11 to 20 cm, and then filling the middle gap of the anode with electrolyte blocks; covering the anode with electrolyte blocks, and welding a double-layer shunt plate on the intermediate pole steel claw; (5) roasting start. The present invention has the advantages of high safety factor, good roasting quality, low labor intensity, and reduced coke particle consumption. The disadvantages are that when only coke particles are used for laying, the corners are extremely poorly conductive, the temperature is too low, and the roasting is insufficient.

[0005] Patent No. CN101956216A discloses a method for baking an aluminum electrolytic cell with a special cathode structure, wherein a mixture of graphite particles and coke particles is used as a baking medium, and before baking, the cathode surface and the boss surface are respectively filled with a baking medium composed of a mixture of graphite particles and coke particles in different proportions for leveling, and then powered on for baking. The invention makes the baking temperature distribution uniform and the temperature step small. The disadvantage is that the coke particles are easy to stick to the anode, resulting in uneven distribution of the anode current. Summary of the invention

[0006] The object of the present invention is to provide a method for uniformly calcining a 500KA fully graphitized electrolytic cell, which can improve the conductivity of the corner electrode, make the current distribution uniform, allow the corner electrode and the cathode lining to be fully calcined, and enhance the stability and cell life of the electrolytic cell.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for uniformly calcining a 500KA fully graphitized electrolytic cell comprises the following steps:

[0009] The grooves between the cathode carbon blocks were filled with cryolite wrapped in plastic film, and the medium was laid on the surface of the cathode boss. The corner poles were laid with a mixture of graphite crushed and coke powder with a mass ratio of 1:6, and the middle poles were laid with pure coke powder with a laying thickness of 20 mm.

[0010] The tank is filled with calcium fluoride, cryolite, soda ash and electrolyte powder;

[0011] Power-on roasting: The roasting time is 5 days. On the first day, the voltage is 2.8-3.6V and the temperature is 150-400℃; on the second day, the voltage is 2.6-3.2V and the temperature is 400-600℃; on the third day, the voltage is 2.4-3.0V and the temperature is 600-800℃; on the fourth day, the voltage is 2.0-2.6V and the temperature is 800-900℃; on the fifth day, the voltage is 1.8-2.4V and the temperature is 900-960℃.

[0012] During the roasting of the existing electrolytic cell, the current distribution of the four corner anodes is generally ≤1mA, and the corner electrode material is basically not melted, resulting in poor conductivity of the corner electrode, too low corner electrode temperature, and insufficient roasting of the corner electrode. In addition, there is also uneven heating of the cathode lining as a whole, and it is difficult to salvage the carbon slag. Based on this, the inventor knows from Joule's law that: Q = I 2 Rt, to increase the heat income, you can increase the current. By continuously optimizing the ratio of graphite crushed and coke powder at the corner pole, find the optimal ratio, graphite crushed: coke powder = 1:6, which can enhance the conductivity of the corner pole during the roasting process while ensuring that the current is not too large, so that the material is fully melted, the cathode lining is evenly heated as a whole, and fully roasted.

[0013] The corner pole is paved with a mixture of 1:6 graphite powder and coke powder, and the middle pole is paved with pure coke powder, which can ensure the uniformity of the temperature rise of the electrolytic cell. At the same time, it can reduce the increase in the cost of using graphite powder to charge the furnace, and can also ensure that the electrolytic cell has sufficient resistivity during the roasting process to increase heat income. It has the advantages of uniform roasting temperature distribution, especially the temperature difference between the roasting end and the edge of the electrolytic cell is significantly reduced. Compared with the electrolytic cell roasting furnace that is fully charged with coke powder, the temperature rise of the electrolytic cell is uniform and stable, the material cost is low, the graphite powder fly ash is less at startup, and the resistivity of the inter-electrode material of the electrolytic cell is appropriate, which ensures the roasting effect. And because the temperature difference between the roasting corners and the edges is small, the early damage caused by uneven thermal stress of the electrolytic cell is avoided, and the cell life is effectively extended.

[0014] The roasting period refers to the interval from the start of power-on to the end of roasting (about 120 hours). The key to management during roasting is temperature, which requires a uniform temperature gradient and uniform anode current distribution. Therefore, the inventors control the voltage and temperature during roasting, allowing the voltage and temperature to change gradually, so that the temperature gradient remains uniform, the anode current is evenly distributed, and the electrolytic cell is fully roasted.

[0015] The cryolite wrapped in plastic film is used to fill the grooves between the cathode carbon blocks. The cryolite is easily dissolved into liquid and fills the cracks between the cathodes, thus reducing the risk of aluminum liquid leakage. Wrapping the cryolite with plastic film helps to form a viscous mixture or precipitate of cryolite melt and alumina. These mixtures or precipitates are formed between the raised walls at the bottom of the cathode, which helps to prevent the cathode aluminum liquid from flowing into the bottom of the tank through the cracks and gaps at the bottom of the tank, thereby extending the life of the electrolytic cell. At the same time, it can also prevent the cryolite from being splashed on the cathode surface, affecting the baking effect of the electrolytic cell.

[0016] Furthermore, when laying the medium on the surface of the cathode boss, first place the frame on the cathode boss, then pour the medium into the frame, scrape it flat, and after laying, the whole is an inverted triangle, and the particle size of coke powder and graphite fragments is 3-6mm. Do not press during the scraping process, scrape from the position close to the leg extension of the electrolytic cell to the center seam, and it is strictly forbidden to scrape back and forth. After scraping, clean up the spilled mixture. Laying starts from A28 and B28 and ends with A1 and B1. Laying in an inverted triangle can save the amount of coke powder. Coke powder produces carbon slag, which indirectly reduces the production of carbon slag and reduces the labor intensity of salvaging carbon slag.

[0017] Further, the steps of filling the tank are as follows: (a) evenly sprinkle calcium fluoride around the sides of the electrolytic cell; (b) lay cryolite or electrolyte powder around the sides of the electrolytic cell, the pole seams and the middle seams, wherein the sides are just covered, the pole seams are filled, and the middle seams are half filled; (c) a mixture is loaded around the sides of the electrolytic cell and the middle seam, wherein the mixture includes soda ash and cryolite / electrolyte powder in a mass ratio of 1:2; (d) the electrolyte powder is added to the poles along the tank, and the electrolyte powder on the poles is loaded to 2 cm from the lower edge of the steel beam. Among them, the amount of calcium fluoride is 1-1.5t, the amount of cryolite or electrolyte powder in step (b) is 6t, the amount of mixture in step (c) is 10-15t, and the amount of electrolyte powder in step (d) is 15-20t. Step (d) of laying the electrolyte powder layer can prevent air from oxidizing the cathode lining and anode, and can save energy by preheating the electrolyte powder, which can significantly reduce the amount of cryolite used and greatly reduce the baking cost. By laying multiple materials and multiple layers, it can prevent the solid conductive material from sintering with the anode and avoid uneven distribution of the anode current. The use of soda ash and calcium fluoride non-conductive materials can also prevent the cathode current from being too concentrated, causing protrusions to fall off and affecting the overall baking effect of the cathode lining.

[0018] Furthermore, 8 thermocouple sleeves are pre-buried in the electrolytic cell while the cryolite is loaded, and the thermocouple sleeves are 5 cm away from the surface of the cathode carbon block. The length of the thermocouple sleeve is about 70 cm, one end of the pipe mouth is sealed, and the other end of the pipe mouth is flattened into a duckbill. One is installed at the aluminum outlet and the slag outlet at the flue end, and the remaining 6 are installed at the corresponding positions of A7, A14, A21 and B7, B14, B21, and do not contact the anode, cathode and any part of the cell body. The thermocouple sleeve is convenient for strengthening the measurement, tracking and processing of the temperature during the roasting period, preventing the cathode from being locally overburned, causing early damage to the electrolytic cell, and ensuring the roasting effect of the electrolytic cell.

[0019] Furthermore, before the power is turned on and the roasting is carried out, the anode is installed and the contact area between the anode and the mixture layer of the corner electrode is maintained at more than 80%. After the anode is stabilized, the gap between the anode guide rod and the horizontal busbar is maintained at 1-3mm. When hanging the electrode, the aluminum guide rod is tilted to face the crossbeam busbar, so that the guide rod contacts the surface of the crossbeam busbar and is put into place vertically by sliding, so that the bottom of the anode sits stably on the mixture of coke particles and graphite fragments, and the anode falls completely on the mixture layer (the bottom of the anode must be placed flat). Ensure that the contact area between the anode and the coke particles is more than 80%. After the anode is stabilized, the gap between the anode guide rod and the horizontal busbar is maintained at 1-3mm, the anode guide rod does not contact the hook, and is located in the middle of the hook.

[0020] Furthermore, before the power is turned on and the roasting is carried out, a shunt plate is installed, and one end of the shunt plate is crimped to the crossbeam busbar of the electrolytic cell with a U-shaped fixture, and the other end is crimped to the column busbar of the next tank with a U-shaped fixture. Since there are many gaps between the coke powders and the electrolytic cell is in a cold state, the total resistance of the coke powder layer is relatively large. If the full current is given to the electrolytic cell at this time, a higher cell voltage will be caused, which will cause a large thermal shock to the lining of the electrolytic cell and easily cause early damage to the electrolytic cell. The shunt plate is mainly used to divert part of the current within a period of time after the start of power-on, avoid the adverse impact of strong current on the cold tank lining, and ensure that the roasting is carried out smoothly. The old-style shunt adopts the method of welding at both ends, which is extremely inconvenient to install and disassemble, and the graded control is extremely difficult to achieve. In the present invention, the two ends of the shunt plate are fixed with bow-shaped fixtures, which are extremely convenient to install and disassemble, and easy to achieve grading. The crossbeam busbar and the column busbar are crimped, the cross-section of the crimping surface is large, and the shunt effect is better.

[0021] Furthermore, before the power is turned on for roasting, it also includes installing a soft connection, fixing one end of the soft connection on the crossbeam busbar with a bow-shaped clamp, and fixing the other end on the anode guide rod with bolts and nuts, so that the contact surface of the soft connection, the guide rod and the busbar is close and seamless. The soft connection is used to pass the current, so that the anode carbon block can maintain good contact with the coke particle layer by its own weight, and prevent the uneven distribution of the anode current; during roasting, the anode will be lifted due to thermal expansion, and the soft connection can be stretched, effectively avoiding the situation where the busbar is lifted and the busbar is uneven. The existing roasting of coke particles is to fix the aluminum guide rod and the anode large busbar together with a small box clamp, which is easy to cause the contact part of the bottom surface of the anode and the coke layer to deviate, resulting in excessive resistance, bias current, high power consumption, and uneven roasting temperature. The use of soft connection technology, due to the scalability of its soft belt and flexible connection method, can keep the anode carbon block equal to the coke particle pressure and absorb thermal deformation, so that the bottom surface of the anode and the coke layer are fully in contact, making it evenly conductive and the roasting temperature uniform.

[0022] Furthermore, the flexible connection is arc-shaped, and the expansion space of the flexible connection is 8cm≤≤20cm. Within this expansion space, it can be ensured that after the anode is heated and expanded, the flexible connection will not be pulled off the beam busbar or drive the horizontal busbar to move upward, thereby avoiding the situation where the busbar is uneven before starting and the anode current is unevenly distributed after starting.

[0023] Furthermore, after 12 hours of power-on roasting, when the cell voltage is lower than 2.8V, the first group of shunts are removed; after the first group is removed, the next group is removed every 4 hours until all are removed. Since U=IR, the voltage will increase when the shunt is removed. When the voltage is lower than 2.8V, the impact voltage generated by removing the shunt will not be too high. While ensuring the current, the impact voltage can be avoided from being too high to damage the cathode, ensuring the roasting effect of the electrolytic cell.

[0024] The technical solution of the present invention has at least the following advantages and beneficial effects:

[0025] In the present invention, a specific ratio of graphite fragments to coke powder is used to improve the conductivity of the corner electrode, so that the corner electrode material can be fully melted and the corner electrode can be fully roasted, thereby improving the uniformity and sufficiency of the cathode lining roasting, and improving the stability and current efficiency of the electrolytic cell during normal production; avoiding too high a ratio resulting in a large current distribution and serious empty burning of the corner before the start-up time; avoiding too low a ratio resulting in poor conductivity of the corner electrode, too low a temperature, and insufficient melting of the material.

[0026] The corner pole and the middle pole are laid with different media to ensure the uniformity of the electrolytic cell temperature rise, while reducing the cost increase of the graphite crushing furnace, and ensuring that the electrolytic cell has sufficient resistivity to increase heat income during the baking process. The use of multiple materials and multiple layers in the cell can prevent the solid conductive material from sintering with the anode and avoid uneven distribution of the anode current. The use of soda ash and calcium fluoride non-conductive materials can also prevent the cathode current from being too concentrated, causing the protrusion to fall off and affecting the overall baking effect of the cathode lining.

[0027] Control the gradual change of voltage and temperature during roasting to maintain uniform temperature gradient, even distribution of anode current, and sufficient roasting of the electrolytic cell. The two ports of the electrolytic cell are unobstructed, the electrolyte is poured in smoothly, the safety is high, and the normal production corners are avoided. The voltage curve runs well in the later stage of startup, the noise is appropriate, and the cell temperature is controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the average temperature rise curve of the corner anode when the mass ratio of graphite fragments to coke powder is different;

[0029] Figure 2 It is a schematic diagram of the average current distribution curve at different mass ratios of graphite fragments and coke powder;

[0030] Figure 3 Schematic diagram of the heating curves of Example 1 and Comparative Examples 4-6. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0032] Example 1

[0033] A method for uniformly calcining a 500KA fully graphitized electrolytic cell comprises the following steps:

[0034] S1. Fill the grooves between the cathode carbon blocks with cryolite wrapped in plastic film, place the frame on the cathode boss, then pour the medium into the frame, scrape it flat, and lay it in an inverted triangle shape. The corners are laid with a mixture of graphite and coke powder in a mass ratio of 1:6, and the middle is laid with pure coke powder. The laying thickness is 20 mm, and the particle size of coke powder and graphite is 4 mm.

[0035] S2. Install the anode: Keep the contact area between the anode and the mixture layer at the corner electrode to more than 80%. After the anode is placed firmly, the gap between the anode guide rod and the horizontal busbar should be kept at 2mm.

[0036] S3, using calcium fluoride, cryolite, soda ash and electrolyte powder to fill the tank, the steps are: (a) evenly sprinkle 1.5 tons of calcium fluoride around the sides of the electrolytic cell; (b) lay 6 tons of cryolite or electrolyte powder around the sides of the electrolytic cell, the pole seams and the middle seams, wherein the sides are just covered, the pole seams are filled, and the middle seams are half filled; (c) 10 tons of mixed material are loaded around the sides of the electrolytic cell and the middle seam, wherein the mixed material includes soda ash and cryolite / electrolyte powder in a mass ratio of 1:2; (d) add electrolyte powder to the poles along the tank, and the electrolyte powder on the poles is loaded to 2 cm from the bottom of the steel beam, and the amount of electrolyte powder used is 15 tons;

[0037] S4. While installing cryolite, 8 thermocouple sleeves are pre-buried in the electrolytic cell. The thermocouple sleeves are 5 cm away from the surface of the cathode carbon block. One is installed at the aluminum outlet and the slag outlet at the flue end, and the remaining 6 are installed at the corresponding positions of A7, A14, A21 and B7, B14, B21;

[0038] S5. Install the flexible connection: fix one end of the flexible connection to the crossbeam busbar with a bow-shaped clamp, and fix the other end to the anode guide rod with bolts and nuts, so that the contact surface between the flexible connection, the guide rod and the busbar is close to each other without any gap. The flexible connection is arc-shaped, and the expansion space of the flexible connection is 10cm;

[0039] S6. Install the shunt plate: Use a U-shaped fixture to crimp one end of the shunt plate to the crossbeam busbar of the electrolytic cell, and use a U-shaped fixture to crimp the other end to the column busbar of the next cell;

[0040] S7, power-on roasting: the roasting time is 5 days, the voltage is 3.5V and the temperature is 300℃ on the first day; the voltage is 3.0V and the temperature is 500℃ on the second day; the voltage is 2.5V and the temperature is 700℃ on the third day; the voltage is 2.2V and the temperature is 850℃ on the fourth day; the voltage is 2.0V and the temperature is 960℃ on the fifth day.

[0041] After 12 hours of power-on baking, when the cell voltage is lower than 2.8V, remove the first group of tapped wafers; after removing the first group, remove the next group every 4 hours until all are removed.

[0042] Example 2

[0043] In this embodiment, when the power is turned on and the baking is performed, the voltage is 2.8V and the temperature is 400°C on the first day; the voltage is 2.6V and the temperature is 600°C on the second day; the voltage is 2.4V and the temperature is 800°C on the third day; the voltage is 2.0V and the temperature is 800°C on the fourth day; the voltage is 1.8V and the temperature is 900°C on the fifth day. The rest is the same as in Example 1.

[0044] Example 3

[0045] In this embodiment, when the power is turned on for calcination, the voltage is 3.6V and the temperature is 150°C on the first day; the voltage is 3.2V and the temperature is 400°C on the second day; the voltage is 3.0V and the temperature is 600°C on the third day; the voltage is 2.6V and the temperature is 900°C on the fourth day; the voltage is 2.4V and the temperature is 950°C on the fifth day. The rest is the same as in Example 1.

[0046] Comparative Example 1

[0047] In this comparative example, the corner poles were paved with a mixture of graphite chips and coke powder in a mass ratio of 1:9.

[0048] Comparative Example 2

[0049] In this comparative example, a mixture of graphite chips and coke powder in a mass ratio of 1:7 was laid on the corner poles.

[0050] Comparative Example 3

[0051] In this comparative example, a mixture of graphite chips and coke powder in a mass ratio of 1:5 was laid on the corner poles.

[0052] Comparative Example 4

[0053] In this comparative example, the corner pole and the middle pole are laid with the same medium, which is a mixture of graphite crushed and coke powder in a mass ratio of 1:5.

[0054] Comparative Example 5

[0055] In this comparative example, when the power was turned on for roasting, the voltage was 3.8V and the temperature was 450℃ on the first day; the voltage was 3.5V and the temperature was 650℃ on the second day; the voltage was 3.2V and the temperature was 850℃ on the third day; the voltage was 2.8V and the temperature was 950℃ on the fourth day; and the voltage was 2.5V and the temperature was 980℃ on the fifth day.

[0056] Comparative Example 6

[0057] In this comparative example, when the power was turned on for roasting, the voltage was 2.5V and the temperature was 130℃ on the first day; the voltage was 2.4V and the temperature was 350℃ on the second day; the voltage was 2.2V and the temperature was 550℃ on the third day; the voltage was 1.8V and the temperature was 750℃ on the fourth day; and the voltage was 1.5V and the temperature was 880℃ on the fifth day.

[0058] Test results

[0059] The roasting conditions of Example 1 and Comparative Examples 1-3 were tested, and the results were as follows:

[0060] Table 1

[0061]

[0062]

[0063] According to Table 1 and Figure 1-2 It can be seen that the method of Example 1 has a good roasting effect. It shows that when the ratio of graphite fragments to coke powder is 1:6, the roasting quality of the electrolytic cell is good.

[0064] The calcination conditions of Example 1 and Comparative Examples 4-6 were tested, and the results were as follows: Figure 3 The results show that, compared with the comparative example, the temperature gradient during the calcination in Example 1 is more uniform, and the anode current is evenly distributed, which is conducive to the full calcination of the electrolytic cell.

[0065] In summary, the uniform calcination method of the 500KA fully graphitized electrolytic cell provided by the present invention can improve the conductivity of the corner electrode, make the temperature gradient uniform, and evenly distribute the anode current, so that the corner electrode and the cathode lining can be fully calcined, thereby enhancing the stability and life of the electrolytic cell.

[0066] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for uniformly calcining a 500KA fully graphitized electrolytic cell, characterized in that: The following steps are involved: The grooves between the cathode carbon blocks were filled with cryolite wrapped in plastic film, and the medium was laid on the surface of the cathode boss. The corner poles were laid with a mixture of graphite crushed and coke powder with a mass ratio of 1:6, and the middle poles were laid with pure coke powder with a laying thickness of 20 mm. The tank is filled with calcium fluoride, cryolite, soda ash and electrolyte powder; Power-on roasting: The roasting time is 5 days. On the first day, the voltage is 2.8-3.6V and the temperature is 150-400℃; on the second day, the voltage is 2.6-3.2V and the temperature is 400-600℃; on the third day, the voltage is 2.4-3.0V and the temperature is 600-800℃; on the fourth day, the voltage is 2.0-2.6V and the temperature is 800-900℃; on the fifth day, the voltage is 1.8-2.4V and the temperature is 900-960℃.

2. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: When laying the medium on the surface of the cathode boss, first place the frame on the cathode boss, then pour the medium into the frame, scrape it flat, and after laying, the whole is an inverted triangle. The particle size of coke powder and graphite fragments is 3-6mm.

3. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: The steps of filling the tank are as follows: (a) evenly sprinkle calcium fluoride around the sides of the electrolytic cell; (b) lay cryolite or electrolyte powder around the sides, the pole gaps and the middle gaps of the electrolytic cell, wherein the sides are just covered, the pole gaps are filled, and the middle gaps are half filled; (c) fill the mixture around the sides and the middle gap of the electrolytic cell, wherein the mixture includes soda ash and cryolite / electrolyte powder in a mass ratio of 1:2; (d) add electrolyte powder to the poles along the tank, and the electrolyte powder on the poles is filled to 2 cm from the lower edge of the steel beam.

4. According to the uniform roasting method of the 500KA fully graphitized electrolytic cell according to claim 3, it is characterized in that: While the cryolite is being loaded, 8 thermocouple sleeves are pre-buried in the electrolytic cell, and the thermocouple sleeves are 5 cm away from the surface of the cathode carbon block.

5. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: Before the power is turned on for roasting, the anode is installed and the contact area between the anode and the mixture layer of the corner electrode is kept at more than 80%. After the anode is placed firmly, the gap between the anode guide rod and the horizontal busbar is kept at 1-3mm.

6. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: Before power-on roasting, the process also includes installing a shunt plate, crimping one end of the shunt plate to the crossbeam busbar of the electrolytic cell with a U-shaped fixture, and crimping the other end to the column busbar of the next cell with a U-shaped fixture.

7. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: Before the power-on roasting, the process also includes installing a flexible connection, fixing one end of the flexible connection to the beam busbar using a bow-shaped clamp, and fixing the other end to the anode guide rod using bolts and nuts.

8. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 7, characterized in that: The flexible connection is arc-shaped, and the expansion space of the flexible connection is 8cm≤≤20cm.

9. The uniform calcination method of a 500KA fully graphitized electrolytic cell according to claim 1, characterized in that: After 12 hours of power-on baking, when the cell voltage is lower than 2.8V, remove the first group of tapped wafers; after removing the first group, remove the next group every 4 hours until all are removed.